Analysis of Learners’ Perception of the Pedagogical Usefulness of Messenger as a Call Application - Morales-Vázquez, Eleazar; Arias de la Cruz, Andrés (Cinzontle, 2018)
The purpose of this study is to analyze students’ perceptions of the pedagogical usefulness of messenger as a Computer Mediated Communication (CMC) application in second language learning. Our analysis will be presented as follows: first, a discussion of the pedagogical usefulness of CMC in L2 learning; second, an analysis of how our findings are similar or different to previous researches on Computer Mediated Communication (CMC); finally, the benefits and limitations of CMC in reference to other CALL applications.